THE INFLUENCE OF THE AUDIT COMMITTEE, COMPANY SIZE, AUDIT TENURE, AND KAP REPUTATION ON GOING CONCERN AUDIT OPINIONS (EMPIRICAL STUDY OF TRADING, SERVICE AND INVESTMENT COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2020-2022 PERIOD - Anggraeni, Dina; Mareta, Sigit (Jurnal Perspektif Manajerial dan Kewirausahaan (JPMK), 2023)
A going concern audit opinion is an opinion given by the auditor stating whether there is doubt about the entity's ability to continue as a going concern. Going concern problems are complex and continue to exist, so factors are needed that are used as benchmarks in determining a company's going concern status. This research aims to examine the influence of the audit committee, company size, audit tenure, and KAP reputation about current audit opinions. The subjects of this research are trading, service, and investment companies listed on the Indonesian stock market. The sampling method used a purposive sampling technique for 183 companies. The data in this research was collected through non-participant observation methods by downloading data from the IDX. The results of hypothesis testing show that the variables company size and KAP reputation do not affect going concern audit opinion, while the variables audit committee and audit tenure have a significant effect on going concern audit opinion.